2013
DOI: 10.1089/g4h.2013.0004
|View full text |Cite
|
Sign up to set email alerts
|

“Braingame Brian”: Toward an Executive Function Training Program with Game Elements for Children with ADHD and Cognitive Control Problems

Abstract: In the area of childhood attention-deficit hyperactivity disorder, there is an urgent need for new, innovative, and child-focused treatments. A computerized executive functioning training with game elements aimed at enhancing self-control was developed. The first results are promising, and the next steps involve replication with larger samples, evaluating transfer of training effects to daily life, and enhancing motivation through more gaming elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 25 publications
2
59
0
7
Order By: Relevance
“…Each child performed one of three intervention-conditions of 'Braingame Brian' (Prins et al, 2013); a WM-training, a flexibility-training, or a mock-training (Appendix S1 and Figure S3). In each intervention-condition, all EF tasks were performed but whether the level was adaptive differed per intervention-condition.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each child performed one of three intervention-conditions of 'Braingame Brian' (Prins et al, 2013); a WM-training, a flexibility-training, or a mock-training (Appendix S1 and Figure S3). In each intervention-condition, all EF tasks were performed but whether the level was adaptive differed per intervention-condition.…”
Section: Interventionmentioning
confidence: 99%
“…Repetition of monotonous tasks in EF training reduces motivation and increases attritionrates, and adding game-elements enhances motivation, and may improve the training effect (Prins, Dovis, Ponsioen, Ten Brink, & Van der Oord, 2011). We, therefore, used an EF training with game-elements: Braingame Brian (Prins et al, 2013), that showed promising pilot-results in ADHD (Oord, Ponsioen, Geurts, Brink, & Prins, 2012). We expected near-transfer to WM and flexibility respectively, and far-transfer to other EF tasks (inhibition, sustained attention), and to parent's ratings of daily life EFs and behavior ( Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Noble, Best, Sidwell, and Strang (2000) introduced game-elements to explicit drug education, which was evaluated as being more fun than the regular method. In contrast, Prins et al (2013) used evidence-based executive function training principles as the basis for their Braingame Brian. In this cognitive training with game elements the participant trains executive functions, such as working memory and inhibition through a diverse set of puzzles, while walking around in an extensive virtual world.…”
Section: Serious Games For Healthmentioning
confidence: 99%
“…Braingame Brian'' meets the need for a new, child-focused treatment for ADHD as it is the first program that trains three executive functions (working memory, inhibition and cognitive flexibility) at the same time and uses game elements in the training. The first results seem promising, while the future steps involve replication with larger samples, evaluating transfer of training effects to daily life, and enhancing motivation through more gaming elements [25].…”
Section: Supporting Children With Adhdmentioning
confidence: 98%